Analisis Hubungan Kinerja Keuangan Daerah Terhadap Indeks Pembangunan Manusia - Etik Winarni; Rahmi Handayani; Ahmad Soleh (Universitas Batanghari, 2022)
This study analyzed the financial performance conditions of the region and human development indexes (HDI); relationship of regional financial performance to the human development index (HDI) of Jambi Province. The data analysis method used in this study is a descriptive, quantitative, and qualitative method that is ecplanatory with a library research approach, this study uses secondary data in the period 2010-2019. The data source in the research was obtained from the realization report of the JambiVinnsi Provincial ApBD and the Central Statistics Agency (BPS) of Jambi Province as well as other agencies and literature relevant to this research. The data analysis tools used to answer regional financial performance are models of analysis of fiscal decentralization degrees, regional financial dependence, regional independence, PAD effectiveness and PAD efficiency and to look at the influence and relationship of financial performance on human development indexes used multiple regression models and person correlation models. The results showed that the financial performance of the Jambi Provincial Government was included in the low category, this was indicated from the DDF level with sufficient criteria, KKD with very high criteria, KMD with very lack of criteria, and Shopping Compatibility in sufficient criteria. Furthermore, the ratio of fiscal decentralization degrees and direct spending compatibility has a positive and significant effect on provincial HDI, while on the ratio of regional financial dependence, pad effectiveness and efficiency of PAD Jambi Province has no significant effect on HDI in Jambi Province. as well as regional financial independence, direct spending compatibility and degrees of fiscal decentralization are strongly related to HDI while regional independence is weakly related to HDI.